Constructing Awalkway Connecting to the Toilet at the Faculty of Engineering Using Concrete Pavers Department of Civil Engineering. - Muhunga, Kule Charles (Kabale University, 2023)
This report has got all the procedures/activities in walkway construction pavement using concrete paver blocks, for example, setting out paver making and laying of paver blocks There is moulding of paver blocks, process, and materials used, and curing.